Systemic antibiotic therapy in periodontal diseases - Fattahy Meybody, Samira; Sulashvili, Nodar; Sulashvili, Marika; Matoshvili, Maia (Caucasus Journal of Health Sciences and Public Health, 2018)
Periodontitis is inflammation of periodontal tissues that it can has much different microbial etiology. This periodentium inflammation treated in the way of nonsurgical treatment and mechanical debridement and regular pattern of periodontal care the only indication is for the patient to improve visual approach for mechanical debridement. Quite high list of systemic antibiotic are published for treatment of periodontal therapy that some of them are effect in high clinical result while others do not. This has resulted in discussion for the role of systemic antibiotics in treatment of periodontitis while the recent researched shows evidence-base assessment for use of antibiotics for relevant treatment .the objective aims of this research is to provide an update information for use of systemic antibiotics on clinical issues for periodontal therapy.